ANALYSIS OF THE EFFECT OF GROSS DOMESTIC PRODUCT, FINANCIAL DEVELOPMENT, FOREIGN DIRECT INVESTMENT, AND ENERGY ON CO2 EMISSIONS IN INDONESIA FOR THE 1990-2020 PERIOD - Pratama, Ikhwan Annas; Panjawa, Jihad Lukis (Transpublika Publisher, 2022)
This study examines the factors influencing CO2 emissions from 1990 to 2020. In this study, CO2 emissions are the dependent variable, and the independent variables consist of financial development, foreign direct investment, economic growth, and energy, as measured by the Error Correction Model (ECM) method implemented in the E-views 10 software. This study discover that (1) Financial Development in the short and long term has no effect on carbon dioxide (CO2) emissions in Indonesia, (2) foreign direct investment in the short and long term has no effect on carbon dioxide (CO2) emissions in Indonesia, (3) economic growth in the short and long term has an insignificantly positive effect on carbon dioxide (CO2) emissions in Indonesia, and (4) energy has no effect on carbon dioxide (CO2) emissions in Indonesia.